Career Decision-Making Self-Efficacy and Career Preparation Behavior: Evidence from Final-Year Undergraduate Students - Patricia Bena Kristianto; Missiliana Riasnugrahani (Journal of Economics and Management, 2026)
Career preparation has become a critical developmental task for final-year undergraduate students, particularly as they transition from higher education to the labor market. However, many students face difficulties in preparing for their careers effectively. In this context, Career Decision-Making Self-Efficacy (CDMSE) is considered a key psychological resource that may influence students’ Career Preparation Behavior (CPB). This study aims to examine the role of Career Decision-Making Self-Efficacy in predicting Career Preparation Behavior among final-year undergraduate students. A quantitative approach was employed with a sample of 394 final-year undergraduate students from various universities in Bandung City. Data were collected using the Indonesian versions of the CDMSE-Ind and CPB questionnaires. Participants were recruited through non-probability snowball sampling. Data analysis was conducted using logistic regression to assess the effect of CDMSE on CPB. The findings reveal that Career Decision-Making Self-Efficacy has a significant positive effect on Career Preparation Behavior. Students with higher levels of CDMSE tend to engage more actively in behaviors that support career readiness. This study highlights the importance of self-efficacy in career decision-making as a determinant of career preparation among undergraduate students. This study contributes to the literature by examining a culturally adapted model of CDMSE within Indonesian collectivist context. The findings suggest that higher education institutions should develop structured and targeted career development programs to enhance students’ self-efficacy and support their transition into the workforce.